Theology of the Church: New Horizons - Veliath, Dominic (Journal of Dharma, 2006)
Kuncheria Pathil, Theology of the Church: New Horizons, Bangalore: Dharmaram Publications, 2006, pages 230, ISBN: 81-86861-90-4.